Pengembangan Sistem Informasi Penggalangan Donasi pada Yayasan Gerakan Nurani Orang Tua Asuh (GN-OTA) Kabupaten Lumajang - Yuris Socio Perestroika; Adam Hendra Brata; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
GN-OTA Foundation is a non-profit organization focused on funding education for underprivileged school-aged children. GN-OTA is now experiencing a decline in the number of donations since apart from the foundation of the Foster Parents National Movement. To help overcome these problems, an information system was developed to raise donations and publications for GN-OTA foundation. The author proposes the development of this information system based on the phenomenon of e-charity, online fundrising or donations made via the internet which is quite successful in increasing social sensitivity in the community. The development of this system utilizes the Iterative development model with an object oriented approach. This system applies the concept of MVC (Model View Controller). Meanwhile, the tests performed are functional tests based on white-box and black-box testing models. Functional test shows good results, visible from the valid results for each test scenario. In addition to functional testing, the authors also tested the non-functional aspects of performance by using the tool YSlow. YSlow is an online tool that can test and assess system performance. YSlow gives a pretty good result C for average performance for donation page. However, in terms of the minimum HTTP request test matrix, this system still need improvement.